Industries and Global Competition A History of Business Beyond Borders - Bouwens, Bram; Donzé, Pierre-Yves; Kurosawa, Takafumi (Taylor & Francis, 2017)
Changes in the dynamics of economic activities since the last decades of the 20th century have yielded major changes in the composition of industries and the division of labor and production across different regions of the world. Despite these shifts in the global economy, some industries have remained competitive even without relocating their operations overseas. Industries and Global Competition examines how and why the specificities of certain industries and firms determined their choice of location and competitiveness. This volume identifies the major drivers of this process and explains why some firms and industries moved to other parts of world while others did not. Relocation was not the sole determinant of the success or failure of firms and industries. Indeed some were able to reinvent themselves at their original location　and build new competitive advantages. The path that each industry or firm took varied. This book argues that the specific characteristics of each industry defined the conditions of competitiveness and provide a wide range of cases as illustrations.